Development of zeolite catalysts for the conversion of natural gas to ultraclean liquid fuel - Saidina Amin, Nor Aishah (Faculty of Chemical and Natural Resource Engineering, 2007)
The use of crude oil as the feedstock for gasoline production has a major drawback due to depleting oil deposits. On the contrary, natural gas is available in abundance; therefore, it is considered to be a more attractive alternative source for gasoline production. Extensive research efforts have been devoted to the direct conversion of methane to higher hydrocarbons and aromatics. The transformation of methane to higher hydrocarbons and aromatics has been studied under oxidative and non-oxidative conditions. The chemical equilibrium compositions of methane oxidation to higher hydrocarbons have been calculated using the minimum total Gibbs energy approach. The results showed that the conversion of methane increased with oxygen concentration and reaction temperature, but decreased with pressure. In term of catalyst development, it was found that the W-H2SO4/HZSM-5 catalyst prepared with acidic solution showed the highest activity for the conversion of methane to gasoline in the absence and presence of oxygen. The performance of the Li modified W/HZSM-5 catalyst was improved which was attributed to the suitable amount of Brönsted acid sites in the catalyst. The dual reactor system which consisted of OCM and oligomerization reactors was also investigated. The result yielded liquid fuels comprising of C5-C10 aromatics and aliphatics hydrocarbons. In another approach dual bed system was studied and it was found that Ni/H-ZSM-5 was a suitable catalyst for the conversion of methane to gasoline products. Kinetic studies on methane conversion in the presence of co-feeds ethylene and methanol to produce higher hydrocarbons in gasoline range was performed. The reaction rate increased when methane concentration in the feed mixture decreased. The correlation between experimental and calculated reaction rate indicates that the model fits the data well.